Comparison of Bilirubin Level in Term Infants Born by Vaginal Delivery and Cesarean Section Delivery - Hakim (Hekmati), Pohanwal Doctor Abdul; Shah (Akbari), Pohanwal Doctor Said Ali (Journal for Research in Applied Sciences and Biotechnology, 2024)
Background: Given the overriding importance of neonatal jaundice and scarcity of studies on the role of route of delivery on its occurrence, this study aimed to investigate the association between neonatal bilirubin level and the route of delivery (i.e., normal vaginal delivery [NVD] and cesarean section [CS]). Methods: This prospective, cross-sectional study was conducted in 2012- in Accadmic hospital of medical faculty of balkh university Afghanistan, in all term infants, who met the inclusion criteria was serum bilirubin level was measured by the bili-test device between the second and seventh days after birth. In cases with skin bilirubin level>5 mg/dl, serum bilirubin was also checked. Results: A total of 182 neonates were enrolled in the study, 56% of whom were male. The mean bilirubin levels in the NVD and CS groups were 9.4±2.9 mg/dl and 9.8±3.4 mg/dl, respectively (P=0.53). Additionally, comparison of the mean bilirubin levels between the two groups based of demographic characteristics demonstrated no significant differences. Conclusion: This study showed no significant correlation between neonatal jaundice in term infants and the route of delivery.